Consequences of the use of methylphenidate without medical prescription by university students (Research, Society and Development, 2022)
Central Nervous System (CNS) stimulant drugs, such as amphetamines, dextroamphetamines and methylphenidate (MPH), are drugs used mainly in the treatment of Attention Deficit Hyperactivity Disorder. In this sense, such medications are elements capable of raising the user's wakefulness, which demonstrates an improvement in mood and cognitive performance. This fact makes them increasingly sought after for the “recreational” mode, where they illicitly seek to increase their disposition as an aid to better academic and professional performance. In this context, the present study aimed, through an integrative review, to evaluate the use of Methylphenidate in academics without medical prescription and what are the main consequences that this inadequate consumption can cause in the human body. Thus, although the use of MPH promotes concentration, attention, disposition and energy, its indiscriminate use also causes changes in the wakefulness and mood of its users. Thus, the individual starts to present adverse effects such as changes in heart rate, bouts of insomnia and psychosis. The excessive use of psychotropic drugs is related to economic, social, clinical and educational aspects of consumers. Therefore, pharmacists, doctors and health professionals should assist in carrying out awareness campaigns, pamphlets and lectures.